Nilai-Nilai Yang Terkandung Pada Tradisi Mitoni Adat Jawa di Desa Tanjung Sawit Kecamatan Tapung Kabupaten Kampar - Sisilia Pramesti; Idawati (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
Tanjung Sawit Village, Tapung District, Kampar Regency's Javanese Mitoni heritage.  Suhartini & Baharudin (2021), namely the values of cooperation, entertainment, morality, religion, and beauty.  Descriptive analysis using a qualitative approach is the methodology employed in this study.  Observation, interviews, and documentation are the methods of data collecting employed in this study. According to the study's findings, beauty is typically defined as something that other people can appreciate visually, like two coconuts cut into the shape of a puppet.  The religious significance derived from a traditional Mitoni practice is praying together to ask Allah for protection. In addition, praying together, one asks Allah SWT to ensure that the newborn is healthy, good, and loyal to his parents, and that he is endowed with excellent things in his environment. One of the moral principles found in the Mitoni traditional practice is sungkeman, which entails expressing regret and requesting prayers from both parents to facilitate the delivery process and to ensure the baby is born healthy and with excellent morals.  Breaking a coconut, purportedly to ascertain gender, is part of its entertainment value.  In the Mitoni traditional culture, collaboration takes the form and value of neighbors working together to assist run the event successfully until it is ended. For instance, cooking in the kitchen and serving food, rujak, and cendol to ensure the celebration runs properly.  This collaborative effort exemplifies the benefits of teamwork in this Mitoni procession.